Broken homes and empty pantries: The impact of couple separation on living standards in France - Julia Mink (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
This study sheds new light on the impact of couple separation on living standards by considering the effects of separation on measures reflecting the adequacy of food consumption in addition to more commonly studied income and expenditure measures. Using panel data from France, I examine changes in disposable income, food expenditure and food quantities purchased, diet quality and body weight at the time of separation and up to eight years later, compared to a control group of households that did not separate. Living standards decline to such an extent that households cannot maintain their food consumption, resulting in weight loss.
Keywords: D12; J12; 330; Separation; divorce; living standards; income; food consumption; event study